PERSEPSI PEMANFAAT TERHADAP KINERJA LEMBAGA UED-SP AL-RIZKI DI DESA KAMPUNG PULAU KECAMATAN RENGAT KABUPATEN INDRAGIRI HULU - Acriski '; Susy Edwina; Shorea Khaswarina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Economic Business Village Save-Loans (UED-SP) according to Regulation No.06 of 1998 is an institution that is engaged in the savings and loan and belong to village community / urban village are cultivated and managed by village communities / urban village. The purpose of this study to determine: (1) institutional effectiveness as perceived by users of UED-SP. (2) Efficient use of resources is based on the perception of users UED-SP. (3) Sustainability institution based on the perception of users UED-SP. The sample in this study the beneficiary of funds UED-SP In the Kampung Pulau Village SubdistrictRengatIndragiri Hulu Regencyamounting to 34 people with the selection of Simple Random Sampling. Analysis of the performance institutions UED-SP was measured using a Likert's Summated Rating Scale (LSRS). Institutions Performance UED-SP based on the perceptionusers belonging to "Medium" score 3.10. The effectiveness the institution has been able to achieve its goals independently in performing their duties and to consult with the community in planning the program. Efficiency Resource Allocation already efficient seen from conformity amount funds received by the realization that reducing the amount arrears and the level of congestion funds. Sustainability institute based indicator the ability to independently without government assistance, revolving funds, capable of creating jobs and capable of being economic institutions.   Keywords: Effectiveness, Efficiency, Perception, Sustainability, UED-SP